Pathophysiology of Trousseau’s syndrome - Dicke, C.; Langer, F. (Hämostaseologie, 2015)
Clinically relevant clotting abnormalities in cancer patients are referred to as Trousseau’s syndrome. While thrombotic complications such as venous thromboembolism are most frequent in every day’s practice, cancer patients may also experience severe bleeding symptoms due to complex systemic coagulopathies, including disseminated intravascular coagulation, haemolytic thrombotic microangiopathy, and hyperfibrinolysis. The pathophysiology of Trousseau’s syndrome involves all aspects of Virchow’s triad, but previous basic research has mainly focused on the cellular and molecular mechanisms underlying blood hypercoagulability in solid cancers and haematological malignancies. In this regard, over-expression of tissue factor (TF), the principal initiator of the extrinsic coagulation pathway, by primary tumour cells and increased shedding of TF-bearing plasma microparticles are critical to both thrombus formation and cancer progression. However, novel findings on intrinsic contact activation in vivo, such as the release of polyphosphates or DNA by activated platelets and neutrophils, respectively, have pointed to additional pathways in the complex pathophysiology of Trousseau’s syndrome.
Keywords: Cancer; thrombosis; tissue factor; factor VII; microparticles